2020
DOI: 10.1007/s42399-020-00485-9
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Current Repurposing Drugs for the Treatment of COVID-19: Reality and Challenges

Abstract: The coronavirus disease 2019 (COVID-19) caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a global pandemic with a high growth rate of confirmed cases. Therefore, therapeutic options are desperately urgent to fight with this damning virus. As it may take years to develop a specific therapy of COVID-19, it is urgent to emphasize the repurposing of drugs used for other conditions. This study reviewed the most common drugs for COVID-19 based on available online literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 72 publications
0
64
0
Order By: Relevance
“…Moreover, CQ inhibits the viral RNA and DNA polymerase, virion assembly, and viral shedding ( Fig. 1 ) [ 16 ]. CQ can interact with the LV/RTV in COVID-19 patients, and cause the prolongation of the QT interval [ 131 ].…”
Section: Chloroquine/hydroxychloroquine Azithromycin and Coronavirumentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, CQ inhibits the viral RNA and DNA polymerase, virion assembly, and viral shedding ( Fig. 1 ) [ 16 ]. CQ can interact with the LV/RTV in COVID-19 patients, and cause the prolongation of the QT interval [ 131 ].…”
Section: Chloroquine/hydroxychloroquine Azithromycin and Coronavirumentioning
confidence: 99%
“…In addition, there are specially approved treatment strategies for urgent use during the COVID-19 pandemic despite the lack of substantial data. These emergency treatment strategies include the use of remdesivir and convalescent plasma in the USA and favipiravir in China [ [14] , [15] , [16] ]. Along with trials of different treatment options, several vaccine candidates are under evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite ongoing intensive research on prevention, control and management of COVID-19 pandemic, no known specific and effective drugs or vaccines have been developed to manage or prevent COVID-19 [1][2][3]. Therefore, many drugs have been evaluated in its management and the search continues.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many drugs have been evaluated in its management and the search continues. Hosseinet al, [1] reported that based on the preliminary data from clinical trials and considering the National Institute of Health (NIH) and Food and Drug Administration (FDA) recommendation, remdesivir and convalescent blood products are the most promising potential for COVID-19 treatment. The group [1] added that the uses of chloroquine, hydroxychloroquine, favipiravir, ivermectin, and colchicine might also be effective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation